Pemberdayaan kader kesehatan tentang latihan gerak range of motion (ROM) - Andri Yulianto; Reni Tri Subekti; Tiara Tiara (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Shoulder joint disorders in the elderly such as frozen shoulder, stiffness, pain, and reduced range of motion can hinder daily activities, diminish independence, and impact quality of life. Limited access to rehabilitation services in rural Thailand necessitates strengthening promotive and preventive services delivered by village health volunteers, who play a strategic role within the community. Purpose: To empower health volunteers to understand, practice, and educate the community on safe range-of-motion (ROM) exercises for the elderly. Method: This international community service activity was conducted over three days in the partner village in Thailand. Twenty-four individuals comprising village health volunteers and community representatives involved in basic community health services participated in the program. The activity aimed to build participant capacity, enabling them to understand, practice, and disseminate education regarding ROM exercises for the elderly. Participant knowledge was assessed using a questionnaire, while skills were evaluated through direct observation during ROM practice simulations. The activity was evaluated based on four key indicators: increased knowledge through health education, improved skills through ROM training, the participants' ability to perform ROM exercises independently, and their ability to educate the community on ROM exercises. Data are presented descriptively using frequencies, percentages, and mean scores. Results: The proportion of participants in the